THE IMPACT OF SCHOOL WORK CLIMATE ON TEACHER PROFESSIONAL DEVELOPMENT: STUDY AT PRIVATE JUNIOR HIGH SCHOOL - Wawan Karsiwan; Tia Fajartriani; Dtakiyyatuddaaimah; Rizky Choerudin (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Teacher professional development is an important factor in improving learning quality, yet its effectiveness is influenced by the school work climate. This study aimed to analyze the relationship between school work climate and teacher professional development in private junior high schools in Bogor Regency. The research employed a quantitative correlational method with a cross-sectional design involving 100 non-civil servant teachers selected through total sampling. Data were collected using Likert-scale questionnaires that had met validity and reliability standards. Data analysis included descriptive statistics, Pearson correlation, and multiple linear regression. The findings showed that both school work climate and teacher professional development were categorized as high. There was a strong positive relationship between school work climate and teacher professional development (r=0.72; p<0.001). Innovation support was the strongest predictor, followed by principal leadership, collegial relationships, and system clarity, while workload had a negative effect. These five dimensions explained 58% of the variance in teacher professional development. The study highlights the importance of a supportive school work climate in promoting sustainable teacher professional development